Hubungan Pengetahuan Ibu Hamil Trimester III Dengan Keteraturan Pemeriksaan Kehamilan Di Klinik Bersalin Ramlah Parjib 3 Kota Samarinda - Sholihah, Ani Mar’atus; Fijri, Bayu (Bunda Edu-Midwifery Journal (BEMJ), 2020)
The health status of a country is determined by several indicators one of which is the Maternal Mortality Rate (MMR) is still quite high 228 / 100,000 live births, while the MDG target in 2015 MMR can be reduced to 102 / 100,000 live births. the direct cause of maternal death in Indonesia is bleeding Data from the Samarinda City Health Office shows that the maternal mortality rate in 2012 was 75 / 100,000 live births. The death rate was due to bleeding 20 / 100,000, 5 / 100,000 due to hypertension in pregnancy and 50 / 100,000 live births due to others such as asthma, heart, hepatitis and others. Clarifying pregnant women in the status of mild, moderate and severe risk cannot be used as a benchmark anymore, because all pregnant women are at high risk, even in normal pregnancy, in labor complications can occur without being predicted beforehand, therefore every pregnant woman must examine herself thoroughly regularly and get optimal midwifery services supported by a good attitude of midwives. A good attitude of midwives during providing midwifery services to every pregnant woman is a real strategy in an effort to increase motivation of pregnant women on the importance of regular pregnancy checks. This study aims to determine the relationship of maternal knowledge with regular third trimester pregnancy examinations at the Ramlah Parjib Maternity Clinic in Samarinda. This study uses descriptive analytical research method to determine the relationship of maternal knowledge with regular third trimester pregnancy examinations at the Ramlah Parjib 3 Clinic Samarinda, with a cross sectional study design. The population in this study was third trimester pregnant women who examined their pregnancies at the Ramlah Parjib 3 Maternity Clinic in Samarinda, by convenience sampling amounting to 32 respondents. Based on statistical tests between the two pregnancy rate variables a statistical test is performed using the chi square formula, it is known that the value of chi square X2 is calculated (24.5) and P value is 0.00 while the price of chi square (X2) table is at db = 3-1: 2, at the 0.05 significance level (alpha) is 5.591, this means that the X2 count lebih dari X2 table or P value kurang dari of alpha, it can be concluded that there is a significant relationship between the knowledge of pregnant women and the regularity of the examination. From this study it was concluded that there was a significant relationship between the knowledge of pregnant women and the regularity of examinations at the Ramlah Parjib III Samarinda clinic. And it is hoped that all parties interested in improving the health status of pregnant women can further enhance antenatal care services or pregnancy examinations so as to achieve maximum and better results for the future.